Contribution of hydraulically lifted deep moisture to the water budget in a Southern California mixed forest. Issue 4 (25th November 2013) - Kitajima, Kuni; Allen, Michael F.; Goulden, Michael L.
Abstract [1] Trees and shrubs growing in California's mountains rely on deep roots to survive the hot and dry Mediterranean climate summer. The shallow montane soil cannot hold enough water to support summer transpiration, and plants must access deeper moisture from the weathered bedrock. We used the HYDRUS‐1D model to simulate the moisture flux through the soil‐plant continuum in Southern California's San Jacinto Mountains. The mechanisms facilitating deep water access are poorly understood, and it is possible that either or both hydraulic lift and capillary rise contribute to the survival and activity of trees and soil microorganisms. We modified HYDRUS to incorporate hydraulic lift and drove it with meteorological and physiological data. The modeled quantity of water lifted hydraulically ranged from near zero during the wet months to 28 mm month−1 in midsummer. Likewise, modeled capillary rise was negligible during the winter and averaged 15 mm month−1 during June through November. Both mechanisms provided water to support evapotranspiration during the dry months. Isotopic measurements of xylem water for eight shrub and tree species confirmed the importance of a deep source of water. Conventional and automated minirhizotron observations showed that fine‐root and rhizomorph biomass remained relatively constant year‐round, while mycorrhizal hyphae biomass varied markedly, peaking in the wet season and declining by 70% in the dry season. Model results predict that hydraulic lift and capillary rise play key roles in Southern California's mountains: they support evapotranspiration and photosynthesis during the summer drought; they contribute to the year‐round survival of fine roots and soil microorganisms.